CHANGES IN THE PHYSICAL SETTING OF OPEN SPACE IN ACCOMMODATING A VARIETY OF ACTIVITIES IN THE CREATIVE KAMPONG OF DAGO POJOK - Ivena, Priska (Jurnal Riset Arsitektur, 2017)
Abstract-The development of a given settlement or residential area cannot be detached from the phenomenon of the urban kampong succeeding in holding out, based on the concept of harmoniously living together as members of a community in society, and one of the strategies used is keeping a close-knit community. The city of Bandung with its concept of being a creative city supports the idea of having creative kampongs that promote the arts and culture of the local community. The creative kampong is expected to be able to provide solutions by creating a better environment, and one of these solutions is exploiting the potential of the natural and human resources available to improve the local community’s welfare. The aim of this research study is to determine how exactly the community living in the creative kampong of Dago Pojok has been able to enhance the physical setting of a limited amount of space in such creative ways to fulfill the need for a range of activities. The method used for this research project can be classified as qualitative by way of frequent mapping of the physical setting at the creative location selected, based on the outcome of observation and recommendations made by the actual initiator of the creative kampong. This stage was followed by mapping of activities and behavior or attitude in the area under observation over a certain period of time. In order to find out more about the physical setting during incidental activities, the data were obtained from the documentation of the creative kampong. The processed data were subsequently analyzed to determine to which degree the need for activities in a particular physical setting can be attempted by way of creative aspects. In the open space used for everyday activities and creative pursuits, the physical setting initially influenced the activities themselves, and the varied activities went on to provide a context for creativity in the same manner as a physical setting experiences change in keeping with the need for space. The physical elements that undergo change may be categorized as fixed, semi-fixed, and non-fixed elements, and those situated in the open (public) space may be classified as base plane, vertical plane, street accessories, illumination and the scope-related atmosphere.Keywords: change in physical setting, open space, creative kampong, Dago Pojok Kampong